A Step Toward Digital Inclusion in Agriculture : Managing ICT Capacity-Building and Measuring Outcomes Among Smallholder Farmers - Babu, Jampala Maheshchandra; Yadav, Arun; Shivnani, Tina (Indian Journal of Finance, 2025)
Purpose : This study examined the impact of ICT training on small-scale farmers’ adoption of digital agricultural technologies in India. It assessed the effectiveness of focused capacity-building initiatives on their digital participation. Methodology : Primary data was collected through structured surveys before and after training in Jaipur Tehsil, Rajasthan. The sample included diverse socio-demographic profiles. A comparative analysis assessed changes in digital tool use, while factor analysis identified key dimensions of digital adoption. Descriptive statistics and comparative metrics measured shifts in engagement. Findings : ICT training significantly improved farmers’ digital engagement, especially in government portals, mandi apps, and eNAM. Trust in digital tools and expert consultations also increased, though crop protection and pest control app usage remained low. Practical Implications : The study highlighted the need for ongoing literacy initiatives to address structural digital disparities and facilitate inclusive agricultural digital transformation. Originality : The study identified structural barriers influencing ICT use among small-scale farmers by combining socio-demographic variables with digital engagement. Pre-training responses revealed a digital divide, with minimal engagement in government agriculture websites, mandi apps, and weather forecast tools. Farmers preferred traditional knowledge sources due to trust, digital literacy, and cost. Following the training, government websites, social media apps, and eNAM portals experienced increased usage, while farmer-to-expert consultations and video conferencing also rose, indicating growing confidence in digital tools. Younger and more educated farmers were more likely to adopt these applications, while gender disparities persisted due to limited digital accessibility. The intervention effectively enhanced digital adoption and improved adaptability.